Pengaruh Senam Lansia Terhadap Tingkat Kecemasan Lansia di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman Tahun 2013 - Herawati, Novi (Jurnal Keperawatan Jiwa, 2014)
Anxiety is defined as difficult or distress which is a normal consequence of growth, change, new experiences, the discovery of identity, and the meaning of life. Physical and psychological changes experienced by the elderly as part of the aging process, can cause anxiety in the elderly themselves. If the low-level anxiety is not addressed it will be panic. One way that can cope with the anxiety in the elderly is the gymnastics elderly. The purpose of the study to look at the effect of exercise on anxiety levels of elderly. The study design experiment, with one group pretest - posttest design. Respondent number 19 is obtained through purposive sampling technique. Data collection was performed before and after exercise elderly. Univariate and bivariate analyzes by paired t - test with a significance level of alpha = 0.05 level. The results showed no significant difference between the average elderly anxiety before and after exercise. Prior to gymnastics on average 2.79, median 3, standard deviation of 0.787. After gymnastics gained an average of 1.95, a median of 2, the standard deviation of 0.780. It is expected that this can be done the elderly exercise on a regular basis to the elderly who experience anxiety and as a preventative measure for the elderly in general.